Diagnostic Performance of Sex-Specific Modified Metabolite Patterns in Urine for Screening of Prediabetes - Li, Zaifang; Zhang, Yanhui; Hoene, Miriam; Fritsche, Louise; Zheng, Sijia; Birkenfeld, Andreas; Fritsche, Andreas; Peter, Andreas; Liu, Xinyu; Zhao, Xinjie; Zhou, Lina; Luo, Ping; et al. (Frontiers in Endocrinology, 2022)
Aims/hypothesis: Large-scale prediabetes screening is still a challenge since fasting blood glucose and HbA1c as the longstanding, recommended analytes have only moderate diagnostic sensitivity, and the practicability of the oral glucose tolerance test for population based-strategies is limited. To tackle this issue and to identify reliable diagnostic patterns, we developed an innovative metabolomics-based strategy deviating from common concepts by employing urine instead of blood samples, searching for sex-specific biomarkers, and focusing on modified metabolites. Methods: Non-targeted, modification group-assisted metabolomics by liquid-chromatography-mass spectrometry (LC-MS) was applied to second morning urine samples of 340 individuals from a prediabetes cohort. Normal (n=208) and impaired glucose tolerant (IGT; n=132) individuals, matched for age and BMI, were randomly divided in discovery and validation cohorts. ReliefF, a feature selection algorithm, was used to extract sex-specific diagnostic patterns of modified metabolites for the detection of IGT. The diagnostic performance was compared with conventional screening parameters fasting plasma glucose (FPG), HbA1c, and fasting insulin. Results: Female- and male-specific diagnostic patterns were identified in urine. Only three biomarkers were identical in both. The patterns showed better AUC and diagnostic sensitivity for prediabetes screening of IGT than FPG, HbA1c, insulin, or a combination of FPG and HbA1c. The AUC of the male-specific pattern in the validation cohort was 0.889 with a diagnostic sensitivity of 92.6% and increased to an AUC of 0.977 in combination with HbA1c. In comparison, the AUCs of FPG, HbA1c and insulin alone reached 0.573, 0.668, and 0.571, respectively. Validation of the diagnostic pattern of females showed an AUC of 0.722, which still exceeded than the AUCs of FPG, HbA1c, and insulin (0.595, 0.604, 0.634, respectively). Modified metabolites in the urinary patterns include advanced glycation end products (pentosidine-glucuronide, glutamyl-lysine-sulfate), microbiota-associated compounds (indoxyl sulfate, dihydroxyphenyl-gamma-valerolactone-glucuronide). Conclusions/interpretation: Our results demonstrate that the sex-specific search for diagnostic metabolite biomarkers can be superior to common metabolomics strategies. The diagnostic performance for IGT detection was significantly better than routinely applied blood parameters. Together with recently developed fully-automatic LC-MS systems, this opens up future perspectives for the application of sex-specific diagnostic patterns for prediabetes screening in urine.